2019
DOI: 10.13102/rscdauefs.v9i0.3685
|View full text |Cite
|
Sign up to set email alerts
|

Dados sociodemográficos, condições de saúde e sinais de violência contra idosos longevos

Abstract: Este estudo objetivou identificar a relação entre dados sociodemográficos, condições de saúde e sinais de violência e maus tratos contra idosos longevos. Trata-se de um estudo exploratório descritivo com abordagem quantitativa, realizado em cinco unidades básicas de saúde de Vitória da Conquista/ BA, amostra de 310 idosos com idade superior a 80 anos. O instrumento foi constituído de dados sócios demográficos, condições de saúde e índice de avaliação de maus-tratos e abuso a idosos. No grupo Indicadore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Some studies, including a systematic review, also reiterated the information that elders with suggestive cognitive deficit alterations are more likely to undergo some type of violence ( 12 , 15 , 22 ) . This disagreement with our research can be due to the population studied, denoting the need for further research that detail this phenomenon, presenting an overview of this relationship between violence and cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, including a systematic review, also reiterated the information that elders with suggestive cognitive deficit alterations are more likely to undergo some type of violence ( 12 , 15 , 22 ) . This disagreement with our research can be due to the population studied, denoting the need for further research that detail this phenomenon, presenting an overview of this relationship between violence and cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the caregiver burden increases the greater the functional dependence of the old person 30 . Furthermore, studies have linked impairment of functional capacity to the risk of violence, as well as signs of violence in this population [35][36][37] . Maia et al 38 they also reported that the old person who suffers some type of violence is in a situation of functional dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Houve predominância do sexo feminino (61,8%), e isto pode estar relacionado a maior longevidade das mulheres em relação aos homens, a feminilização do envelhecimento e diferenças quanto as atitudes em relação a doenças, visto que as mulheres procuram mais os serviços de saúde (8) . Ainda, encontrou-se que (36,4%), dos idosos são viúvos, predomínio também verificado em estudos desenvolvidos anteriormente (14)(15)(16) , o que pode inferir que, quanto maior a expectativa de vida brasileira mais idosos o país possui, deste modo, maior é a chance de um dos parceiros idosos vivenciarem o falecimento do outro, o que favorece ao elevado número de viúvos na presente pesquisa.…”
Section: Discussionunclassified